Secondary students’ mathematical reasoning in terms of learning styles on online learning - Fresha Anjani; Syafika Ulfah (Jurnal Elemen, 2022)
Since COVID-19 was declared a global pandemic, learning has shifted from face-to-face to online. It is a novel environment, particularly in Indonesia. This study aims to determine the profile and correlation between students' mathematical reasoning abilities and learning styles in online learning. The research method used was quantitative. The population was grade VIII students studying in public Junior High School (JHS) in DKI Jakarta province. The sample was 400 respondents, consisting of 208 males and 192 females, using random cluster sampling. To identify the relationship between mathematical reasoning ability and learning style, to be more specific, the researchers took a sample of one class consisting of 39 respondents. The research instrument was in the form of a questionnaire and mathematical ability test questions in the form of a description. The data analysis technique used descriptive statistics and correlation analysis. The results showed that: (1) the tendency of students' mathematical reasoning abilities was included in the medium category, (2) students had varied learning styles, namely visual, auditory, and kinesthetic learning styles (3) the tendency of students learning styles of public JHS in DKI Jakarta is visual learning style with a percentage of 32.25% as many as 129 students from 400 respondents, (4) there is a significant relationship between mathematical reasoning abilities and student learning styles with a Pearson correlation score of 0.565, and the relationship between the two variables is included in the category of moderate correlation. In this case, choosing a suitable learning approach can impact students' ability to think mathematically.